Representation of the 1916 National Liberation Movement in Drama - Islambayeva, З.У. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The scientific article analyzes the dramatic works written in the middle of the last century, describing the national liberation uprising, the formation of Soviet power in the Kazakh land. The creative search of writers whose works are aimed at revealing the meaning of historical events is considered in detail. Taking as a basis historical dramas where the historical image of the Kazakh Batyr Amankeldi Imanov «Amangeldi» G.Musrepov and «Banner over the steppe» Sh.Kusainova, the researcher points to the important ideas of the authors to reveal the heroic personality of the national hero. He also analyses image of Tokash Bokin, the protagonist of Z. Shashkin’s play «So the era began», who led the Kazakh people during the revolution, became a leader for young people seeking freedom from oppression. The author, based on reliable facts reveals the consequences of the civil war at the beginning of the last century for society and human life in the Kazakh land, the consequences of the development of the soviet system for the Kazakh nation. The social place of positive and negative characters in the studied works was revealed taking into account the peculiarities of their character and social status. The author of the article considers the views of playwrights at the time of writing the play in a modern concept. Also did not remain without attention and not logical drawing up by playwrights of a chain of events in works.